Seasonal diversity of butterflies and its relationship with woody-plant resources availability in an Ecuadorian tropical dry fores - Castro Gil, J. (2017)
Understanding the seasonal community structures of highly diverse animal taxa and how they interact with plants is necessary for efficient conservation efforts such as rapid biodiversity inventory protocols and monitoring programs. This knowledge is partic ularly important for seasonal tropical dry forests, which are among the most threatened ecosystems on the planet. We sampled a seasonal tropical dry forest over the course of a year to determine the period of greatest butterfly richness. Additionally, we e valuated availability of potential woody plant trophic resources (flower buds, blossoms, unripe fruits, ripe fruits, and foliage) in relation to butterfly richness and comm unity composition. Twenty of the 22 species collected showed flight activity between January-April (rainy season), coinciding with maximum plant resources availability. Lepidoptera species richness correlated positively with amount of ripe fruits and foliage. Community composition changes among sample dates involved losses and gains, and not turnovers, of species. These shifts correlate with seasonal oscillations in the variety of ripe fruits and the amount of foliage. Our results indicate that rapid inventory protocols may be applied in the period of Februar y-March; species richness monitoring can be restricted to the rainy season (saving labor and economic costs); and ripe fruits and foliage may be suitable candidates for temporal plant-butterfly interaction surveillance. © Castro, A. and Espinosa, C.